Circ_RPPH1 facilitates progression of breast cancer via miR-1296-5p/TRIM14 axis - Jing Jiang; Shenghong Shi; Wei Zhang; Chao Li; Long Sun; Qidong Ge; Xujun Li (Cancer Biology & Therapy)
Circular RNA Ribonuclease P RNA Component H1 (circ_RPPH1) and microRNA (miRNA) miR-1296-5p play a crucial role in breast cancer (BC), but the molecular mechanism is vague. Evidence showed that miR-1296-5p can activate tripartite motif-containing 14 (TRIM14). Clinical indications of eighty BC patients were collected and the circ_RPPH1 expression was detected using real-time quantitative PCR. MCF-7 and MDA-MB-231 cells were transfected with overexpression or knockdown of circ_RPPH1, miR-1296-5p, or TRIM14. Cell counting kit-8, cell cloning formation, wound healing, Transwell, and flow cytometry assays were performed to investigate the malignant phenotype of BC. The dual-luciferase reporter gene analyses were applied to reveal the interaction between these target genes. Subcutaneous tumorigenic model mice were established with circ_RPPH1 overexpression MDA-MB-231 cells in vivo; the tumor weight and volume, levels of miR-1296-5 and TRIM14 mRNA were measured. Western blot and immunohistochemistry were used to detect TRIM14 in cells and mice. Circ_RPPH1 levels were notably higher in BC patients and have been found to promote cell proliferation, invasion, and migration of BC cells. Circ_RPPH1 altered cell cycle and hindered apoptosis. Circ_RPPH1 knockdown or miR-1296-5p overexpression inhibited the malignant phenotype of BC. Furthermore, miR-1296-5p knockdown reversed circ_RPPH1’s promotion effects on BC. Interestingly, TRIM14 overexpression counteracts the inhibitory effects of miR-1296-5p overexpression and circ_RPPH1 silencing on BC. Moreover, in BC tumor-bearing mice, circ_RPPH1 overexpression led to increased TRIM14 expression and facilitated tumor growth. Circ_RPPH1 enhanced BC progression through miR-1296-5p/TRIM14 axis, indicating its potential as a biomarker and therapeutic target in BC.